Optimization and Evaluation of Patchouli (Pogostemon cablin Benth.) Leaf Essential Oil Gel using Carbopol and Triethanolamine - Marbun, Sertika Handayani; Maimum, Maimum; Maharini, Indri (Jurnal Kefarmasian Indonesia, 2024)
The essential oil of Patchouli (Pogostemon cablin Benth.) has antioxidant activity and can be used as an active compound in sunscreen preparations. The index used to describe the effectiveness of sunscreen products is the Sun Protection Factor (SPF). Patchouli oil has never been developed as a sunscreen in gel dosage form. The exploration of patchouli oil is more about testing antioxidant and antibacterial activity. This research aims to optimize the formula and test the SPF (Sun Protection Factor) value of essential oil of Pogostemon cablin gel preparations. Formula optimization using Simplex Lattice Design 13 contained in Design Expert software. The variables optimized in this study were carbopol and triethanolamine concentrations. The responses used in the optimization process are pH, viscosity, adhesion, and spreadability. The optimum formula was evaluated by evaluating the preparation, including organoleptic, homogeneity, pH, viscosity, adhesive power, spreadability, stability, and SPF value test using the UV-Vis spectrophotometric method. The results showed that the optimum formula composition was obtained from a combination of 0.5% carbopol and 0.7% triethanolamine. The optimum formula gel preparation has a yellow appearance and smell typical of patchouli oil, homogeneous, the pH of the preparation is 6.29 ± 0.08, the viscosity of the preparation is 44086.67 ± 1510.69, the adhesive power is 7.62 ± 0.68, the spreadability of 5.42 ± 0.08, stable. The optimum formula gel preparation has an ultra-protection SPF value of 28.87 ± 0.27.